CEO characteristics and the amount of capital raised in Malaysian IPOs - Badru, Bazeet Olayemi (Inderscience Enterprises Ltd., 2017)
This study examines the impact of the characteristics of the Chief Executive Officer (CEO) on the amount of capital raised in the Malaysian Initial Public Offering (IPO) market. To have a broader picture of the impact, the current study employs the Ordinary Least Squares (OLS) and quantile regression techniques, using a sample of 214 IPOs over the period of 2005-2015. The use of the quantile regression technique allows the study to estimate the impact of the CEO's characteristics at different quantiles of the conditional distribution of the capital raised. The results show that companies with a Malay CEO raise more capital than those companies with a non-Malay CEO. In addition, CEO age is significant and negatively associated with capital raised. However, the impact of CEO educational qualification is mixed, while CEO gender is insignificant. Other variables, such as company size and pre-IPO financial health, have significant and positive impact on capital raised. The practical implication of the study is that the characteristics of the CEO play a signalling role in IPO decisions. As such, investors can consider the characteristics of the CEO before making investment decisions.